Neutral Lipids in the Study of Relationships of Members of the Family Micrococcaceae - Morrison, Susan J. (1971)
The organisms studied were those of the family Micrococcaceae which cannot participate in genetic exchange with Micrococcus luteus and those whose biochemical and physiological characteristics appear to bridge the genera Staphylococcus and Micrococcus. The hydrocarbon compositions of M. luteus ATCC 4698 and Micrococcus sp. ATCC 398 were shown to be similar to those previously reported for many M. luteus strains, consisting of isomers of branched monoolefins in the range C25 to C31. However, Micrococcus sp. ATCC 398 differed somewhat by having almost all C29 isomers (approximately 88% of the hydrocarbon composition). Micrococcus spp. ATCC 401 and ATCC 146 and M. roseus strains ATCC 412, ATCC 416, and ATCC 516 contained the same type of hydrocarbon patterns, but the predominant hydrocarbons were within a lower distribution range (C23 to C27), similar to Micrococcus sp. ATCC 533 previously reported. The chromatographic profile and carbon range of the hydrocarbons of an atypical strain designated M. candicans ATCC 8456 differed significantly from the hydrocarbon pattern presented above. The hydrocarbons were identified as branched and normal olefins in the range C16 to C22. Studies of several different strains of staphylococci revealed that these organisms do not contain readily detectable amounts of aliphatic hydrocarbons. The members of the family Micrococcaceae have been divided into two major groups based on the presence or absence of hydrocarbons. With the exception of M. candicans ATCC 8456, this division corresponded to the separation of these organisms according to their deoxyribonucleic acid compositions.